Edukacyjna rola Kopalni Soli »Wieliczka« - wczoraj i dziś - d'Obyrn, Kajetan; Przybyło, Jerzy (Wydawnictwa AGH, 2013)
During the past centuries, the educational character of the »Wieliczka« Salt Mine was gradually shaped. Only European elites were familiar with the issues of exploiting the Wieliczka salt deposits in the 16th and 17th centuries. After the First Partition of Poland, the Austrian managers of the Salt Mine began to arrange trails for mass tourism. After Poland regained independence, special bonds connected the Salt Mine with the Academy of Mining (presently called the AGH University of Science and Technology). At the end of the 1990s and at the beginning of the 21st century, the educational field trips were based on a network of documented sites and the nature reserve called the Crystal Grottoes. Since 2009, the trips follow the route called »The Mysteries of the Wieliczka Mine«. Apart from the AGH University of Science and Technology, classes were also organised for the students of the Jagiellonian University, Pedagogical University of Cracow, University of Wroclaw, Adam Mickiewicz University, University of Silesia, University of Warsaw, and Silesian University of Technology (2001-2012). Foreign students were coming from Kosice, Ostrava, Parma, or Vienna. Approximately 4,800 students participated in field trips and internships in the 'Wieliczka' Salt Mine between 2001 and 2012.

Przez stulecia istnienia Kopalni Soli »Wieliczka« stopniowo kształtowała się jej rola dydaktyczna. W wiekach XVI-XVII z zagadnieniami eksploatacji złoża zapoznawały się europejskie elity. Po pierwszym rozbiorze Polski austriaccy zarządcy kopalni rozpoczęli organizować trasy dla masowej turystyki. Po odzyskaniu niepodległości bliskie związki połączyły kopalnię z Akademią Górniczą (późniejszą Akademią Górniczo-Hutniczą). Pod koniec lat 90. XX i w początkowych latach wieku XXI edukacja w kopalni bazowała na sieci stanowisk dokumentacyjnych przyrody nieożywionej oraz rezerwacie Groty Kryształowe. Od 2009 roku oparto ją na trasie »Tajemnice wielickiej kopalni«. W latach 2001-2012 na terenie kopalni odbywały się zajęcia dla studentów Akademii Górniczo-Hutniczej, Uniwersytetu Jagiellońskiego, Uniwersytetu Pedagogicznego w Krakowie, Uniwersytetu Wrocławskiego, Uniwersytetu Poznańskiego, Uniwersytetu Śląskiego, Uniwersytetu Warszawskiego, Politechniki Śląskiej, a także studentów z zagranicy, m in. z uniwersytetów w Koszycach, Ostrawie, Parmie i Wiedniu. W latach 2001-2012 praktyki odbyło około 4800 studentów.
The educational role of the »Wieliczka« Salt Mine - past and present
Geology, Geophysics & Environment
Keywords: Wieliczka Salt Mine; Kopalnia Soli Wieliczka; salt deposits; złoże soli kamiennej; education; edukacja; teaching; dydaktyka; geotourism; geoturystyka